Nuclear Exportin 1 (XPO1) Binds to the Nuclear Localization/Export Signal of the Turnip Mosaic Virus NIb to Promote Viral Infection - Zhang, Mingzhen; Gong, Pan; Ge, Linhao; Li, Yinzi; Chang, Zhaoyang; Qiao, Rui; Zhou, Xueping; Wang, Aiming; Li, Fangfang (Frontiers in Microbiology, 2022)
The nuclear localization signal (NLS) and nuclear export signal (NES) are key signatures of proteins for controlling nuclear import and export. The NIb protein of turnip mosaic virus (TuMV) is an RNA-dependent RNA polymerase (RdRP) that is absolutely required for viral genome replication. Previous studies have shown that NIb is a nucleocytoplasmic shuttling protein and contains four putative NES and four putative NLS motifs. Here, we analyzed the function of these NESs and NLSs, and identified two functional NESs and one functional NLS. Mutation of the identified functional NESs or NLS inhibited viral RNA accumulation and systemic infection. Exportin 1 (XPO1) is a nuclear export receptor that binds directly to cargo proteins harboring a leucine-rich NES and translocates them to the cytoplasm. We found that XPO1 contains two NIb-binding domains, which recognize the NLS and NES of NIb, respectively, to mediate the nucleocytoplasmic transport of NIb and promote viral infection. Taken together, these data suggest that the nucleocytoplasmic transport of NIb is modulated by XPO1 through its interactions with the functional NLS and NES of NIb to promote viral infection.